INTENSITY OF SPECIFIC SENSITIZATION AND IMMUNE PROFILE IN PATIENTS WITH BRUCELLOSIS - N. S. Sarkisуan (SPb RAACI, 2016)
The authors propose a new methodological approach to rapid intensity assessment of specific sensitization in acute brucellosis. This technique shows high sensitivity (98%), and specificity (97%). We revealed a direct relation between the intensity of specific IgE-dependent sensitization accompanied by development of immunosuppressive state in patients with brucellosis, i.e., a mean reduction of total CD3+ cell counts by 17.9%; CD3+CD4+ cells, by 13.3%; CD16+CD56+, by 4.4%. Phagocytic ability of blood neutrophils was decreased by 25.8%. The study has shown that an increased reagin-dependent sensitization in brucellosis is closely associated with emergence of severe immunosuppression.